International diversification with securitized real estate and the veiling glare from currency risk - Tim Alexander Kroencke; Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper analyzes diversification benefits from international securitized real estate in a mixed-asset context. We apply regression-based mean-variance efficiency tests, conditional on currency-unhedged and fully hedged portfolios to account for foreign exchange risk exposure. From the perspective of a US investor, it is shown that first, international diversification is superior to a US mixed-asset portfolio, second, adding international real estate to an already internationally diversified stock and bond portfolio results in a further significant improvement of the risk-return trade-off and, third, considering unhedged international assets could lead to biased asset allocation decisions not realizing the true diversification benefits from international assets. Our in-sample results are quite robust in out-of-sample analysis and when investment frictions like short selling constraints are introduced.
urn:nbn:de:bsz:180-madoc-31406
Keywords: G11; G12; G15; 330; Diversification Benefits; International Mixed-Asset Portfolios; Currency Hedging; Spanning Tests; Short Selling Constraints